Chemical, Biological and Scheduled Waste Safety Short Course - Anon (Universiti Malaysia Perlis (UniMAP), 2011)
The short course was organized by Universiti Malaysia Perlis (UniMAP), 9th - 11th November 2010 at Dewan Kuliah Kubang Gajah 4, Universiti Malaysia Perlis.